2021
DOI: 10.26226/morressier.615c7f2662ba8657678b0a3e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19 Pandemic and Its Impact on Perinatal Outcomes Between Symptomatic and Asymptomatic Women

Abstract: Coronavirus disease 2019 (COVID-19) has been increasing among pregnant women worldwide. Its impact on maternal, fetal, and neonatal health is still scarce in the published literature. As a routine COVID-19 prenatal screening has been established for all women requiring hospitalization, it is not clear whether symptomatic women carry worse pregnancy outcomes than those without symptoms. We aimed to analyze perinatal outcomes between symptomatic and asymptomatic women admitted to our center. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Another study in Cameroon reported 64% of pregnant women with COVID-19 were 25-35 years old (Dingom et al, 2020). On the contrary, out of 12 articles in this study, two stated the higher portion of COVID-19 cases in pregnancy was in the AMA group (Babic et al, 2022;Minisha et al, 2022). This might be explained by social factors, such as the likelihood that older women will encounter sick older relatives and children who are left in their care at home (Minisha et al, 2022).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Another study in Cameroon reported 64% of pregnant women with COVID-19 were 25-35 years old (Dingom et al, 2020). On the contrary, out of 12 articles in this study, two stated the higher portion of COVID-19 cases in pregnancy was in the AMA group (Babic et al, 2022;Minisha et al, 2022). This might be explained by social factors, such as the likelihood that older women will encounter sick older relatives and children who are left in their care at home (Minisha et al, 2022).…”
Section: Discussioncontrasting
confidence: 53%
“…Over the past ten years, the trend of delaying childbearing has become more prevalent, particularly in developed nations (Mills & Lavender, 2011). According to the Indonesia Demographic Health Survey (IDHS), this circumstance also occurred in Indonesia in 2013 (BKKBN, BPS, KEMENKES., 2013). AMA can increase the risk of adverse maternal outcomes such as stillbirth, preeclampsia, preterm birth, and fetal distress (Cavazos-Rehg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%